Paths to Knowledge Management in Small and Medium-Sized Hotels - Kim , Mik; Zhang , Wusheng (Journal of Law and Governance, 2008)
The purpose of this paper is to investigate what path options can facilitate small and medium-sized hotels’ knowledge management? And how the options are realised by them? In order to answer these questions, this study undertook an empirical investigation into the current status and practice of knowledge management in small and medium-sized hotels. The empirical investigation was performed through thirteen face-to-face in-depth interviews with owners and managers in small and medium-sized hotels. While the interview method is selected so as to answer the questions, secondary data are utilised to support this study such as in defining the research questions and informing the study findings. This study observed that there were four broad approaches to the way in which hotels put their paths to knowledge management. Each type of the paths is named as: Match, Combination, Divergence, and Specialisation. As arguably, knowledge management is both part of the cost of doing business and the most likely source of competitive advantage, it is as important to the sole operator as to the large corporation. By understanding the different options, hotels will be able to make better decisions in the choice of their suitable paths to knowledge management.